Maritime Security in the Eastern Mediterranean: Kiel International Seapower Symposium 2017 - Stöhs, Jeremy; Bruns, Sebastian (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
The Mediterranean is once again on top of the international community's agenda, returning as the Mare Nostrum of our time with a host of maritime security challenges and various seapower opportunities. This book provides fresh perspectives on the geopolitics of the Eastern Mediterranean and its geoeconomics. It discusses the role of regional stakeholders – such as Israel, Egypt, and Iran – and addresses the challenges for the U.S. Navy and the U.S. Marine Corps. The book will be of special relevance to policy-makers, strategists, intelligence professionals, academics, military thinkers, and those individuals with a deeper interest in the Eastern Med alike.Dr. Sebastian Bruns is the Head of the Center for Maritime Strategy & Security (CMSS) at the Institute for Security Policy, Kiel University (ISPK).Jeremy Stöhs is a security and defense analyst at the Institute for Security Policy and its adjunct Center for Maritime Strategy & Security.